Diagnostic Performance of Angiography-Based Fractional Flow Reserve for Functional Evaluation of Coronary Artery Stenosis - Li, Changling; Leng, Xiaochang; He, Jingsong; Xia, Yongqing; Jiang, Wenbing; Pan, Yibin; Dong, Liang; Sun, Yong; Hu, Xinyang; Wang, Jian'an; Xiang, Jianping; Jiang, Jun (Frontiers in Cardiovascular Medicine, 2021)
Background: A new method for calculating fraction flow reserve (FFR) without pressure-wire (angiography-derived FFR) based on invasive coronary angiography (ICA) images can be used to evaluate the functional problems of coronary stenosis. Objective: The aim of this study was to assess the diagnostic performance of a novel method of calculating the FFR compared to wire-based FFR using retrospectively collected data from patients with stable angina. Methods: 300 patients with stable angina pectoris who underwent ICA and FFR measurement were included in this study. Two ICA images with projections >25° apart at the end-diastolic frame were selected for 3D reconstruction. Then the contrast frame count was performed in an angiographic run to calculate the flow velocity. Based on the segmented vessel, calculated velocity and aortic pressure, AccuFFRangio distribution was calculated through the pressure drop equation. Results: Using FFR≤0.8 as a reference, we evaluated AccuFFRangio performance for 300 patients with its accuracy, sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV). Comparison of AccuFFRangio with wire-measured FFR resulted in an area under the curve (AUC) of 0.954 (per-vessel, p<0.0001). Accuracy for AccuFFRangio were 93.7% for Pa set from measurement and 87% for Pa=100 mmHg in this clinical study. Overall sensitivity, specificity, PPV, NPV for per-vessel were 90%, 95%, 86.7%, 96.3% and 57.5%, 97.7%, 90.2%, 86.3%, respectively. Whereas, overall accuracy, sensitivity, specificity, PPV and NPV for 2-dimensional (2D) quantitative coronary angiography (QCA) were 63.3%, 42.5%, 70.9%, 34.7% and 77.2%, respectively. The average processing time of AccuFFRangio was 4.30±1.87 min. Conclusions: AccuFFRangio computed from coronary ICA images can be an accurate and time-efficient computational tool for detecting lesion-specific ischemia of coronary artery stenosis.